2015
DOI: 10.1080/10668926.2014.917596
|View full text |Cite
|
Sign up to set email alerts
|

“Dangerous Work”: Improving Conditions for Faculty of Color in the Community College

Abstract: This qualitative investigation of the experiences of faculty of color at community colleges identifies current conditions for this population and suggests potentials for ameliorating conditions that inhibit their job satisfaction. We argue that the current conditions for faculty of color, based upon their expressed experiences at the community colleges, are deleterious to their professional performance, to their positive self-image, and to their contributions to their institutions. Alterations to these current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Many Faculty of Color bear the onus of educating their white counterparts about the deleterious effects of racism and whiteness in education policy and practice (Gibson, 2019; Laura, 2019). For Faculty of Color, the burden of unveiling institutional racism and white patriarchy can lead to racial battle fatigue and is often undervalued and uncompensated by tenure review boards and white colleagues (Bridget & Winkle-Wagner, 2017; Croom, 2017; Garrison-Wade et al, 2012; Gibson et al, 2017; Haynes et al, 2020; Levin et al, 2015; Tanner, 2019). Racial battle fatigue pushes many Faculty of Color out of the profession, further perpetuating their underrepresentation in academia (Chancellor, 2019; Rollock, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Many Faculty of Color bear the onus of educating their white counterparts about the deleterious effects of racism and whiteness in education policy and practice (Gibson, 2019; Laura, 2019). For Faculty of Color, the burden of unveiling institutional racism and white patriarchy can lead to racial battle fatigue and is often undervalued and uncompensated by tenure review boards and white colleagues (Bridget & Winkle-Wagner, 2017; Croom, 2017; Garrison-Wade et al, 2012; Gibson et al, 2017; Haynes et al, 2020; Levin et al, 2015; Tanner, 2019). Racial battle fatigue pushes many Faculty of Color out of the profession, further perpetuating their underrepresentation in academia (Chancellor, 2019; Rollock, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested that representation of racialized and Indigenous faculty can additionally combat stereotypes about the educational aspirations of marginalized groups, and can help white students and faculty gain deeper understanding and appreciation for different cultures and perspectives (Linthicum, 1989;Opp & Smith, 1994). Despite this, qualitative research with faculty of colour at U.S. community colleges reveals that they continue to face institutionally based systematic barriers that negatively impact their professional experience, selfimage, and performance (Levin, Jackson-Boothby, Haberier, & Walker, 2015).…”
Section: Is Diversity More Than Employment Equity?mentioning
confidence: 99%
“…The emotions of managing white students are eclipsed, however, with the emotional labor required to mentor historically underrepresented students. Julie Shayne (2017) describes emotional labor as “supporting [structurally and institutionally marginalized] students as they experience alienation, marginalization, and trauma, which prevent them from working to their full potential.” This type of emotional labor, studies show, is often uncompensated, unrecognized, and undervalued ( Bellas 1999 ; Wong 2007 ; Green 2015 ; Levin et al 2015 ; Matthew 2016 ; Pabon 2016 ). It is interesting, for example, that during training sessions and faculty meetings I have heard the phrase “I’m not a therapist” in response to working with students experiencing personal challenges.…”
Section: Seeking Guidance About Painful Pedagogymentioning
confidence: 99%